Transient Exertional Compressive Radial Neuropathy in a Collegiate Baseball Pitcher: A Case Report. Issue 4 (8th October 2022) - Wellington, Ian J.; Garvin, Patrick M.; Stelzer, John W.; Morgan, Courtney; Alessi, Anthony; Hall, Matthew; Rodner, Craig; Edgar, Cory
Abstract : Case: A 21-year-old collegiate baseball pitcher presented with transient lateral arm pain and wrist extension weakness after pitching more than 1 inning. Physical examination was unremarkable at rest. Ultrasound-guided injection of the radial nerve at the level of the lateral intramuscular septum improved his symptoms. After decompression of the radial nerve, the patient noted resolution of his symptoms while pitching. Conclusion: Atraumatic radial neuropathy is a rare but documented phenomenon. As far as we know, this is the first reported case of a transient exertional radial neuropathy in an athlete at the level of the lateral intermuscular septum.